La ética publicitaria de las empresas ecuatorianas como responsabilidad social de los grupos de interés - Proaño-González, Esther Angélica; Escobar Quiña, Josselyn Dayana; Gómez Pacheco, María Isabel; Cruz Campos, Diana Carolina (Editorial Grupo AEA, 2024)
This article analyzes the advertising ethics handled by Ecuadorian companies, making a synthesis of the way in which the social responsibility of the entities or officials linked to their advertising practices is involved. This research is carried out due to the constant changes in advertising nowadays, with the objective of deepening how organizations in Ecuador disseminate advertising and how they direct them to interest groups showing social responsibility. For this, it is based on a methodology of bibliographic review being a qualitative research where data are collected to be evaluated from the general to the particular. Thus, the impact of advertising for product awareness and customer attraction that companies or enterprises currently use is observed from all business-commercial activities. In this sense, it is necessary to review the ethics in advertising, the approach to stakeholders, the management of social responsibility as well as its regulation within companies, in order to learn new advertising techniques and methods for companies to comply with responsibility to generate advertising strategies with an ethical approach.